Implementasi Desain Pembelajaran Online di SDN 15 Kota Tangerang pada Masa Pandemi Covid 19 - Rean, Gresia Tuto; Rizkiyanah, Putri; Yeni, Putri; Sakina, Syera Putri (Lembaga Yasin AlSys, 2022)
Implementation is a number of actions carried out by individuals, several high-ranking officials, or government or private groups that are directed at achieving the goals that have been outlined in policy decisions. Design is a designer, training needs to do initial planning for the training program/ learning, designing training materials and planning a conceptual training evaluation which will later be used as the basis for the development stage. SDN 15 CITY OF TANGERANG designs online learning with a learning system that is carried out through personal computers (PCs) or laptops that are connected to an internet network connection. Teachers can do learning together at the same time using groups on social media such as WhatsApp (WA), telegram, Instagram, zoom applications or other media as learning media. Thus, the teacher can ensure that students take part in learning at the same time, even though in different places. Some students who do not have mobile phones study in groups, so that they carry out learning activities together. Start learning through video calls that are connected to the teacher concerned, are asked questions one by one, to take attendance via Voice Note available on WhatsApp. The materials are also provided in the form of videos that are less than 2 minutes long.